Penguatan Administrasi Pemerintahan, Kewilayahan, dan Otonomi Daerah di Bagian Tata Pemerintahan Sekretariat Daerah Kabupaten Solok: Rencana Strategis 2026–2030 - Fahrurrozi Al-Ambari; Syafwandi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study develops a 2026–2030 Strategic Plan for strengthening government administration, regional governance, and regional autonomy in the Government Administration Section of the Regional Secretariat of Solok Regency. Using a SWOT analysis approach, the research identifies internal-external factors in local governance post-Revision of Law No. 23/2014. Qualitative methods were applied through triangulation of interview data, document studies, and observations. Findings indicate core strengths in institutional capacity and regulatory support, while weaknesses include coordination fragmentation and technological limitations. Strategic opportunities lie in digitalization of services and inter-regional collaboration, whereas threats encompass regulatory disparities and fiscal pressures. The strategic plan is formulated through three pillars: (1) Administrative capacity strengthening, (2) Optimization of territorial governance, and (3) Autonomy synergy based on locality. Implementation is designed via a phased roadmap with measurable performance indicators.